To Profit or to Assist? How the Interplay Between Product Recommendations and Relative Prices Impacts Consumers’ Inferences and Choice - Kim, KyuRee; Schrift, Rom Y (Journal of Consumer Research, 2026)
Abstract This article explores the interplay between company-based product recommendation and the product’s relative price. Eight studies demonstrate that consumers are sensitive to the relative price of the recommended option and are more likely to follow the recommendation as its relative price in the choice set decreases. We show that this occurs because consumers use the relative price of the recommended option as a cue for the company’s underlying motives. That is, because consumers generally believe that companies profit more from selling expensive products, they infer that when a company recommends a higher-priced product, its main motivation for doing so is to maximize its profit. Such skepticism about the company’s true motive reduces the likelihood that consumers follow the recommendation. The effect is observed across different types of product categories (hedonic or utilitarian), platforms (offline or online), and recommendations (human- or algorithm-based). Consistent with the proposed account, the effect attenuates when the recommendation comes from an independent and reliable source, when the price-profit link is weakened (i.e., when consumers learn the dissociation between price and profit), when the recommendation is believed to be a signal for popularity, and when consumers have a low innate tendency to question the company’s motivation.